Changes in the immune system in patients with Coronavirus Disease-19 (CoViD-19), Caused by SARS-CoV-2 Virus - Vladimir M Zemskov; Wiktoria Neymann; Konstantin N Pronko; Andrey M Zemskov; Fyodor M Semenov; Amiran Sh Revishvili (Journal of Biology and Medicine - Peertechz Publications, 2020)
Changes in the cellular and humoral links of the immune system of patients with coronavirus disease-19, modifications of laboratory parameters, including biochemical, acute phase, cytokine, interferon systems, etc. are discussed. The problem of the formation of post-infection immunity and the possibility of reinfection of patients recovered is discussed.